Solve for \( u \) \[ -8 u-2=-3(u+4) \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
First, let's simplify the equation step by step. Starting with: \[ -8u - 2 = -3(u + 4) \] Distributing \(-3\) on the right side, we have: \[ -8u - 2 = -3u - 12 \] Now let's move all terms involving \(u\) to one side and constants to the other. We'll add \(3u\) to both sides: \[ -8u + 3u - 2 = -12 \] This simplifies to: \[ -5u - 2 = -12 \] Next, add \(2\) to both sides: \[ -5u = -12 + 2 \] which simplifies to: \[ -5u = -10 \] Now, divide both sides by \(-5\): \[ u = \frac{-10}{-5} \] This gives us: \[ u = 2 \] Thus, the solution for \(u\) is \(2\).